Evaluating the spatial intensity and demographic impacts of wire-snare bush-meat poaching on large carnivores - Loveridge, A.J.; Sousa, L.L.; Seymour-Smith, J.; Hunt, J.; Coals, P.; O'Donnell, H.; Lindsey, P.A.; Mandisodza-Chikerema, R.; Macdonald, D.W. (Biological conservation, 2020)
The bush-meat poaching crisis is a significant threat to biodiversity in tropical forest and savannah biomes, however its impacts on wild animal populations are often difficult to quantify across large spatial scales. Using data from 17 camera trap survey sites in southern Africa, within the Kavango-Zambezi (KAZA) Transfrontier Conservation Area, we show it is possible to assess the demographic impact of wire-snare bush-meat poaching on large carnivore populations, distribution of snaring hotspots and drivers of bush-meat poaching prevalence across this landscape. Results suggest that mortalities in snares may have significant demographic effects on lions (Panthera leo) and spotted hyaenas (Crocuta crocuta) with evidence for population declines and extirpation of large carnivores in the most heavily affected areas. Spatial drivers of bush-meat poaching were found to be a composite of anthropogenic threat scores, environmental resource extraction, protected area size and land-use type. Incidences of snared large carnivores were more prevalent in trophy hunting areas than national parks. Across our study sites, bush-meat poaching has the potential to cause severe declines in populations of large carnivores, particularly in small isolated protected areas surrounded by areas of high human population growth, with resulting loss of regional connectivity and increasing fragmentation of the KAZA landscape. •We used camera surveys to systematically evaluate drivers of bush-meat poaching•Large carnivores are highly susceptible to being trapped in wire snares•Snaring has significant implications for the persistence of carnivore populations•Hotspots snaring of large carnivores correlate closely to anthropogenic factors•Snaring could undermine conservation of extensive multi-use landscape such as KAZA